Implementation of Smart Farming in Horticultural Cultivation Aquaponics Method in Ngeposari Village - Reo Sambodo; Muhammad Asrul; Yosep Tambunan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Ngeposari Village, Semanu District, Gunung Kidul Regency, DIY, is 40 km from the campus. Most people work in the agricultural sector. In particular, the community uses a rain-fed agricultural system. Rain-fed agriculture has limited water availability and relies on rainwater as a source. Rain-fed agricultural land is at high risk of drought. Therefore, through the PPK ORMAWA program, students are trying to contribute, educating the public on agricultural development, through the concept of smart farming in cultivating horticultural plants. The community can implement the concept of smart farming, horticulture, and tilapia cultivation through the aquaponics method. This is an effort to meet the need for healthy food and increase the income of village communities. The program uses a community empowerment system through 3 stages, namely awareness, capacity building and empowerment. The awareness stage is intended to provide understanding and awareness for the community regarding the potential they have and the sectors that can be developed. The community awareness stage is a crucial first step and is the basis for community empowerment. At the capacity building stage, the community is given counseling and assistance to be able to actively implement smart farming as an empowerment stage. Activities were carried out well until the end of the third stage.